Papel da ovariotectomia no aparecimento de sinais histopatológicos associados ao Mal de Alzheimer em camundongos APOE Knockout - Destefani, Afrânio Côgo (2010)
Alzheimer's disease is a progressive degenerative disease that compromises elements of the central nervous system, associated with memory loss and dementia. Are observed in AD extracellular plaques, which consist of deposits of beta-amyloid peptide and intracellular neurofibrillary tangles, which can be associated with intermediate filaments, mainly in the hippocampus and cerebral cortex. Anamnesis and molecular studies have suggested the presence of genetic elements involved in this pathophysiology, such as APOE gene, betaamyloid and TAU beyond glycemic and lipid levels. It is known that the disease incidence increases rapidly with advancing age and Alzheimer's disease affects proportionately more women than men. It is believed that the decline in gonadal hormone levels in postmenopausal women may contribute to the observed difference between the sexes. This study aimed to determine the influence of ApoE and female sex hormones on the molecular aspects involved in the formation of senile plaques in the brain of female mice C57 and ApoE knockout using ovariectomized (OVX) as an agent mimicking menopause in women. We used 14 female mice C57 and 14 female mice ApoEKO (knockout for apolipoprotein E gene) at eight months. There were histological techniques (Cajal, Bielschowsky and Thioflavine S) for the visualization of senile plaques in brain sections. Analysis of plasma glucose, cholesterol, triglycerides, c-HDL, VLDL and LDL were also evaluated. The formation and distribution of βA, Tau protein and Tau [pS199] and BDNF were analyzed via ELISA. The results suggest that ovariectomy promoted the significant depletion of estradiol (E2) and BDNF and significantly increased levels of βA, Tau and Tau [pS199] in different biological compartments when compared to controls. In the meantime, we suggest that female sex hormones along with ApoE modulates the clearance of some molecules related to the formation of senile plaques and neurofibrillary tangles characteristic of Alzheimer's disease.